Studi Semantik Tentang Kesulitan Leksikal Siswa MI NW Darussholihin dalam Memahami Bahasa Sains pada Pembelajaran IPA: Semantic Study on the Lexical Difficulties of MI NW Darussholihin Students in Understanding Scientific Language in Science Learning - Hayaturraiyan (Lembaga Bale Literasi, 2025)
The purpose of this study is to analyze the types and sources of lexical difficulties experienced by students of MI NW Darussholihin in understanding scientific terms in science learning. This research used a qualitative descriptive method with a lexical semantic approach to examine how students construct meaning from scientific vocabulary. Research instruments included a lexical difficulty observation sheet, a semantic-based semi-structured interview guide, and a learning document analysis format. Data were collected through classroom observation, interviews with teachers and students, and analysis of textbooks, worksheets, and student work. Data analysis followed the Miles and Huberman model, comprising data reduction, categorical presentation of difficulties, and conclusion drawing. The findings reveal four forms of lexical difficulty: meaning ambiguity, literal interpretation, unfamiliarity with foreign terms, and transfer from everyday language. These difficulties stem from students' tendency to interpret scientific terms literally and through familiar everyday meanings. The findings underscore the need for learning strategies that emphasize contextual and conceptual meaning-making of scientific language to enhance students' science literacy.